2014
DOI: 10.1371/journal.pone.0099479
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Valence-Space Metaphors: ERP Evidence for Affective Word Processing

Abstract: Embodied cognition contends that the representation and processing of concepts involve perceptual, somatosensory, motoric, and other physical re-experiencing information. In this view, affective concepts are also grounded in physical information. For instance, people often say “feeling down” or “cheer up” in daily life. These phrases use spatial information to understand affective concepts. This process is referred to as valence-space metaphor. Valence-space metaphors refer to the employment of spatial informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
4
10
0
Order By: Relevance
“…This metaphoric association observed in Experiments 1B and 2 is most likely based on attention allocation. Xie et al (2014) adopted a similar paradigm using a 750-ms ISI and found that when spatial targets appeared at the top and bottom of the screen, a larger P200 amplitude was found after positive and negative words, respectively. This P200 may be related to attention allocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This metaphoric association observed in Experiments 1B and 2 is most likely based on attention allocation. Xie et al (2014) adopted a similar paradigm using a 750-ms ISI and found that when spatial targets appeared at the top and bottom of the screen, a larger P200 amplitude was found after positive and negative words, respectively. This P200 may be related to attention allocation.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same 240 affective words as those used by Xie et al (2014) , which were selected from the Chinese Affective Words System (CAWS). Half of them were positive, while the other half were negative ( Wang et al, 2008 ).…”
Section: Experiments 1amentioning
confidence: 99%
“…Furthermore, although the polarity correspondence account holds that the concept-space interaction should be driven primarily by the +polar conceptual category, it has been found that if visual targets follow the concept after brief delays (100 ms), both positive and negative concepts can cause a spatial bias [ 14 ]. Furthermore, the P200 event-related potential (ERP) was modulated by cue-target compatibility after both positive and negative concepts [ 15 ]. These findings support the metaphorical association account, over the polarity correspondence account.…”
Section: Discussionmentioning
confidence: 99%
“…These include explicitly directional words (e.g., "left" and "right", [ 1 , 7 , 8 ]) and words with an implicit spatial meaning. Implicit spatial cues include numbers [ 9 , 10 ], concepts referring to time [ 11 ], concepts with a positive or negative valence [ 12 , 13 , 14 , 15 ], concepts related to social status and self-esteem [ 16 , 17 ], and concepts referring to divinity and evil [ 18 ]. In all these cases, peripheral targets were processed faster at locations compatible with the spatial meaning of the concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been argued that abstract and emotion concepts have sensorimotor properties much like concrete concepts. For example, it has been shown that there is a metaphorical association between emotionally valenced concepts and the vertical plane (e.g., Meier and Robinson, 2004 ; Meier et al, 2011 ; Sasaki et al, 2012 , 2015 ; Santiago et al, 2012 ; Marmolejo-Ramos and Dunn, 2013 ; Marmolejo-Ramos et al, 2013 , 2014 ; Xie et al, 2014 , 2015 ; Damjanovic and Santiago, 2015 ). Most of the work on the association between emotion words and the vertical axis has used visual words as typical experimental stimuli.…”
Section: Introductionmentioning
confidence: 99%